The behavioral finance of MSMEs in the advancement of financial inclusion and financial technology (Fintech) - Asep Risman; Anees Janee Ali; Mochamad Soelton; Indra Siswanti (Universitas Hayam Wuruk Perbanas, 2023)
This study aims to determine empirical evidence of the effect of financial inclusion and financial technology (fintech) on the behavioral finance of MSMEs. This study uses a quantitative method with a positivist paradigm approach. The population of this study is all MSMEs in Indonesia. The sample used in this study is 205 respondents (MSME owners) from all over Indonesia. Sampling is carried out using a random technique. Data collection is carried out by distributing questionnaires, both manually and online using Google Forms, and is measured using a 5-point Likert scale. The data processing is carried out using Partial Least Square (PLS) software with a Structural Equation Modeling (SEM) model. The results of this study show that financial inclusion and financial technology (fintech) have a direct positive effect on the behavioral finance of MSMEs. Financial technology (fintech) can mediate and increase the effect of financial inclusion on the behavioral finance of MSMEs.